A Transfer Learning-based Deep Convolutional Neural Network Approach for White Shrimp Abnormality Classifcation - Orkphol, Korawit; Satianpakiranakorn, Kathawach; Chaihuadjaroen, Jidapa; Valeeprakhon, Tamnuwat (INTERNATIONAL SCIENTIFIC JOURNAL OF ENGINEERING AND TECHNOLOGY (ISJET), 2024)
Shrimp transportation frequently leads to product damage, necessitating a sorting system to identify and remove compromised shrimp prior to processing. This research aims to develop a transfer learning-based deep convolutional neural network system capable of accurately categorizing shrimp into seven classes: Complete body, crunched head, head loss, head loss with remaining chin, cut tail, torn in half, and total crunched. A dataset comprising 405 color shrimp images, each with dimensions of 1,920 x 1,080 pixels, was augmented using geometric transformations to expand the dataset to 6,480 images. These augmented images were then employed to train four state-of-the-art transfer learning-based models (NasNetLarge, InceptionResNetV2, EfcientNetV2L, ConvNeXtXLarge) from Keras Applications. These models also were subsequently compared to a baseline CNN. Results demonstrate that the ConvNeXtXLarge model outperformed the others, achieving the highest accuracy (95%), precision (0.96%), recall (0.95%), and F1-score (0.95%), underscoring its superiority in shrimp damage classification. An analysis of misclassifications revealed potential confusion between certain damage classes, suggesting areas for future refinement to enhance the model’s ability to diﬀerentiate between similar types of damage.